Transcriptomic signatures of subcutaneous adipose tissue in patients with diabetes and coronary artery disease: a pilot study - Doulamis, Ilias P.; Pan, Bernard; Tzani, Aspasia; Plutzky, Jorge; Wong, G. William; Kilic, Ahmet; Wolf, Risa M. (Frontiers in Cardiovascular Medicine, 2025)
The exact role of subcutaneous adipose tissue in the interplay between type 2 diabetes (T2D) and coronary artery disease (CAD) is yet to be determined. A prospective cohort study of adult patients with and without T2D undergoing CABG was performed. Subcutaneous adipose tissue was collected during the procedure and RNA seq analysis was performed. A total of 741 differentially expressed genes (DEGs) were identified (332 up- and 409 down-regulated in the T2D group). Our results demonstrated that pathways related to apoptosis and immune response were significantly dysregulated in the adipose tissue of T2D subjects. The main molecular pathways involved were CXCR, NOTCH, STAT, NFKB1 and FGFR pathways, which have a well-documented role in diabetes and CAD. SPI1 and MTF1 were two novel upstream transcription factors identified which have been suggested to be involved in the inflammatory cascade and insulin regulation in diabetes. Three miRNAs were differentially expressed between the two groups (miR-27a, miR-335 and miR-146). These preliminary results provide fertile ground for further research of potential targets for patients with diabetes and coronary artery disease.